A comparative assessment of the capabilities and success of the wood construction industry in Slovakia and Ukraine based on life cycle assessment certification standards - Delehan, Svitlana; Vilčeková, Silvia; Melehanych, Hanna; Krídlová Burdová, Eva; Khorolskyi, Andrii (Frontiers in Environmental Science, 2024)
This study assessed the possibility of using wood as a building material for the construction of houses. The Life Cycle Assessment method was used as a methodology for assessing the life cycle. Using the One Click LCA and LCC software, the carbon footprint of a log house was calculated for the product life cycle stage mentioned above (A1-A3). When calculating the carbon footprint of wood-based building materials, carbon emissions were taken into account not only from the finished products, but also from all other products obtained as a result of logging. When calculating the carbon footprint, greenhouse gas emissions from all activities are estimated. We have obtained data on the life cycle cost of a wooden house in terms of electricity use. Accordingly, we obtained a value of global warming potential (A1-A3) of 0.51 kg CO2 e/kWh. We also obtained data on the life cycle cost of a wooden house in terms of diesel consumption. According to the results of the LCA, the value of the global warming potential due to meeting the water supply / sewage needs is (A1-A3) 0.69 kg CO2 e/m3. The value of the global warming potential due to meeting the heat supply needs of production needs is (A1- A3) 0.13 kg CO2 e/kWh. Based on the information obtained, we can conclude that it is advisable to use a wooden log house as a building material, as the carbon footprint is smaller than that of a brick building. The final section presents the results of calculating the life cycle cost of a wooden house by discount factor and inflation, the results of the life cycle cost of a wooden house by percentage of energy costs, and the results of assessing the life cycle cost of a wooden house (displaying parameters according to the European energy certification scale). Based on the carbon footprint assessment (using the Life Cycle Assessment methodology), economic comparison (Life Cycle Cost and total construction costs), and expert assessment (based on technical and ergonomic parameters) of the two construction technologies, the feasibility and possibility of using wood as a building material was established.